Pengembangan Aplikasi E-Medical Record Studi Kasus Puskesmas Pagelaran - Deden Rahmat, Asep; Hidayat, Taufik (-, 2025)
In the healthcare world, medical records are a reflection of service quality, with administrative, legal, and other values. The process of medical record management starts from registration, analysis, and storage. The functions of medical records include cost and legal protection. One of the challenges is the slow retrieval of records. The goal of this research is to develop an existing system into a web-based medical record system for public health centers (Puskesmas). Puskesmas play a crucial role in public health services. The system development method used in this research is the Kanban method, which consists of three stages: requirement, development, and testing. The requirement stage involves gathering system needs, analysis, and design using UML. The development stage includes creating the user interface, implementation through Visual Studio Code, and database integration. Meanwhile, the testing stage involves evaluation by both developers and users to assess the performance and usability of the application. The result shows that medical record knowledge plays an essential role in healthcare service quality, legal support, and protection for both patients and healthcare workers. The completeness, integrity, and efficiency of medical record storage are crucial in ensuring quality services and the sustainability of healthcare institutions.